Experiential psychological mechanisms in immersive learning: Presence, embodiment, and engagement as mediator in learning outcomes - Dona Mustika; Dedi Kustandi; Ika Andrini Farida; Iden Rainal Ihsan (Jurnal Inovasi dan Teknologi Pembelajaran, 2026)
Emerging immersive technologies such as Virtual Reality (VR) and Augmented Reality (AR) have driven a transformation in experience-based learning. However, the psychological mechanisms that bridge immersive experiences to learning outcomes have not yet been systematically defined. This study aims to examine and synthesise the roles of presence, embodiment, and engagement as psychological mediators in immersive learning from the perspective of experiential psychology. The method used in this study is a systematic conceptual review, with articles identified using Google Scholar as the data source. The results of the theoretical mapping indicate that direct sensory experience serves as a sensorimotor foundation for evoking a sense of presence. That sense of presence, in turn, supports cognitive and affective engagement. Together, these three components form a mutually reinforcing psychological construct with learning outcomes. Therefore, this study makes a significant conceptual contribution by presenting a more structured and evidence-based framework for designing and evaluating immersive technology-based learning environments.